A Literature Review of EEG-Based Affective Computing in Marketing - Pei, Guanxiong; Li, Taihao (Frontiers in Psychology, 2021)
It is no secret that affect plays an important role in the consumer decision-making process. There is growing interest in the development of new technologies and computational approaches that can interpret and recognize consumers’ affects and will benefit marketing in both academia and industry. From an interdisciplinary perspective, this paper aims to review past studies specifically focused on electroencephalography (EEG)-based affective computing in marketing, which provides a promising avenue for studying the mechanisms underlying affective states and developing recognition computational models to predict the psychological responses of customers. This review offers an introduction to EEG technology and an overview of EEG-based affective computing; provides a snapshot of the current state of the literature; briefly presents the themes, challenges, and trends in the studies of affect evaluation, recognition, and classification; and further proposes potential guidelines to the road ahead for researchers and marketers.